Publication Ethics and Malpractice Statement - Capistrano, Erik Paolo S. (Philippine Management Review; Vol 30 (2023), 2023)
The Philippine Management Review is committed to the highest publication standards and ensuring quality of submissions. Acceptance decisions are based on articles’ significance, originality, clarity, relevance to the journal's scope, and contribution to the body of management knowledge.